Challenges & Issues in Science Teaching At Secondary Level in North Bihar: Investigating Difficulties in Science Learning at the Secondary Level (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The importance of education illuminates the value of education in one's life. Education has a significant impact on our lives because it facilitates the proper progression of our learning, awareness, and ability by altering the personality in order to achieve positive attitudes. Despite the volume of research in the literature on elementary school science education, students continue to face difficulties. The purpose of this paper is to investigate and articulate how students encounter difficulties while learning science. Our study is qualitative in nature and is motivated by phenomenological concerns. The information was gathered through the use of comprehensive semi-structured open-ended questions, and the data were analysed and deduced in detail. This paper will eventually examine the students' personal experiences with this subject. Our study identifies the factors that limit students' desire to study science subjects and desire to improve their in-depth understanding. Additionally, it elucidates the influences of the teacher's actions and factors pertinent to the students that contribute to the students' difficulties. Additionally, it was discovered that the majority of students enjoy learning science subjects and find them interesting. A teacher's characteristics must include professionalism and conscientiousness. He should have sufficient knowledge and mastery of the subjects he tutors and be familiar with cutting-edge techniques. Frequency counts and percentages were used to analyse the data. The paper recommended that regular workshops be organised for all teachers to enable them to effectively manage Integrated Science, that in-service training be included in continuing teacher education, and that teachers be supported to increase their level of confidence when teaching Integrated Science.